2012
DOI: 10.1016/j.ajhg.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Autosomal-Recessive Disease-Causing Mutations in a Founder Population

Abstract: The decreasing cost of whole-genome and whole-exome sequencing has resulted in a renaissance for identifying Mendelian disease mutations, and for the first time it is possible to survey the distribution and characteristics of these mutations in large population samples. We conducted carrier screening for all autosomal-recessive (AR) mutations known to be present in members of a founder population and revealed surprisingly high carrier frequencies for many of these mutations. By utilizing the rich demographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…These studies revealed surprisingly high carrier frequencies for some diseases that had not been recognized as common in the Hutterites (e.g., 1 in 8 Hutterites are carriers for the mutation causing spinal muscular atrophy, [SMA; OMIM 253400]; Chong et al, 2011; Chong et al, 2012). The high participation rate in the study offering CF carrier results indicated that many Hutterites were interested in learning about their carrier status for a monogenic disease.…”
Section: Educational Session and Disclosure Of Individual Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies revealed surprisingly high carrier frequencies for some diseases that had not been recognized as common in the Hutterites (e.g., 1 in 8 Hutterites are carriers for the mutation causing spinal muscular atrophy, [SMA; OMIM 253400]; Chong et al, 2011; Chong et al, 2012). The high participation rate in the study offering CF carrier results indicated that many Hutterites were interested in learning about their carrier status for a monogenic disease.…”
Section: Educational Session and Disclosure Of Individual Research Resultsmentioning
confidence: 99%
“…An invitational flyer described the program and included the title of each talk that would be presented. At the Town Hall we distributed a brochure (Online Resource 3) that described the 14 genetic diseases and their carrier frequencies in the Hutterites (Chong et al, 2012; Gerull et al, 2013) and reviewed autosomal recessive inheritance. The format of the Town Hall consisted of three half-hour presentations.…”
Section: Educational Session and Disclosure Of Individual Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar carrier frequencies due to founder mutations are not uncommon in genetic and geographic isolates. For example, the Limb Girdle Muscular Dystrophy mutation in TRIM32 (p.Asp487Asn) has an estimated frequency of 1 in 6.5 in Hutterite individuals 16. None of 212 chromosomes from 106 random Caucasian individuals carried the c.3335+8A>G mutation.…”
mentioning
confidence: 99%
“…Increased PS intakes have been speculated in the development of many risk factors associated with sitosterolemia. Aside from the basic presentation of xanthomas and premature atherosclerosis in sitosterolemic patients (18, 65, 72), new clinical features such as macrothrombocytopenia (giant platelets with reduced count), hemolytic anemia, splenomegaly and arthritis have been associated with this rare disease (24, 33, 68; Table 1). …”
Section: Trends In Sitosterolemia and Other Risk Factorsmentioning
confidence: 99%